A Phenomenological 4E Eliminative Materialism: Consciousness as Neuromuscular Adaptation “In Virtue of Which” Movement Affordances are Disclosed - Leyva Pizano, Arturo (Journal of NeuroPhilosophy, 2025)
Traditional eliminative materialism has argued that folk-psychological constructs such as belief, desire, or sensation do not correspond to scientifically-real entities. However, eliminativist writing discourse has mostly focused on a purely brain-centered model, with limited clarity on how bodily and environmental factors fit into an ontologically radical perception of the mind. This paper proposes a phenomenological 4E eliminative materialism, drawing on both Rowlands’ arguments for extended, embodied cognition as well as my own focus on neuromuscular adaptation as the basis of consciousness. I argue that “consciousness” should be understood not as mental content but as a fully material phenomenon, realized in the evolving, body-plus-environment synergy “in virtue of which” affordances are disclosed. This perspective dissolves the distinction between “mind” and “body” and even between “brain” and the “rest of the body,” as all cognitive processes rely on bodily structures beyond the brain. The novelty is twofold: (1) consciousness is not “that of which” we are aware, but “that in virtue of which” world-directed actions and perceptions emerge, physically constituted by new neuromuscular dispositions stemming from repeated engagement; and (2) this integrative approach fully eliminates talk of “mental states,” demonstrating that all cognition—and therefore all consciousness—extends beyond the brain. In doing so, it strengthens responses to common eliminativist objections, including self-refutation, by obviating the need for an internal “belief state” behind actions or assertions.